Prediction of physic-chemical property/ Biological Activity and ADMET (absorption, distribution, mechanism, excretion, and toxicity) parameters of approved HIV Medications - Ferrari, I.V.; Mario, M. Di (International Journal of Scientific Research in Biological Sciences, 2022)
The purpose of this short study is to estimate the main chemical-physical properties, pharmacokinetics, and biological activity of the main anti-HIV drugs. The ADMETlab, pkCSM server, and The Pass Online Server were used to complete this computational investigation. The canonical SMILES strings of these compounds were retrieved from PubChem (http://pubchem.ncbi.nlm.nih.gov/) using their CAS registry number or chemical name(s). Regarding the in Silico toxicity study, between all the HIV antivirals investigated, “Lamivudine/Zidovudine”, sold under the brand name “Combivir”, reported good overall values, indicating that it is potentially the least toxic, except for the Minnow toxicity parameter (LC50 with a value of about 7.025 (log mM). Furthermore, Lopinavir also reported overall acceptable values against the various toxicity tests, except that of the Max. tolerated dose (human) with a value of -0.297 (log mg / kg / day in units ), compared to Combivir of 0.684 log mg / kg / day in units. From this evaluation, Combivir is one of the best drugs, manly in terms of toxicity parameters and also it would be useful to focus on discovering similar chemical structures, based on their structure.